Developing reading learning materials for 2nd semester students of international relations department - Azizah, Luthviana; Priyana, Jaka (LingTera, 2021)
This research study aimed to develop reading learning materials to facilitate 2nd-semester students of the International Relations Department in learning reading skills through Bahasa Inggris Hubungan Internasional II subject. This research was a research and development study. The development of the learning materials was carried out through several steps, namely needs analysis, syllabus design, product development, product validation, product revision, try-out, and final product development. This research developed four units of reading learning materials. The appropriateness of the learning materials is viewed from four aspects, namely content, activities, language, and graphics. The expert judgements and field-testing data indicate that the learning materials are appropriate as shown by the mean scores of the expert evaluation ranging from 3.0 to 3.72 and students' agreement ranging from 3.1 to 3.7 on 4 to 1 Likert scale